AD BLOCKING PERSPECTIVES – DRIVERS OF PLEASANT AND UNPLEASANT ONLINE USER EXPERIENCES - Dr. B. V. Jayanthi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
online advertising, which includes models like emails, display advertising, pop ups etc emerged as a handsome source of income to all the stake holders in the last decade. Also referred to as internet advertising or online marketing, this form of advertising is being observed by the market experts from both the marketer and the consumer perspectives across the globe. The social media ad is considered a very cost-effective way of promoting a brand to the digi-savvy consumers. Despite the heavy rise in the digital advertising, the digital advertising environment is not as robust as it ought to have been because of multiple reasons out of which ad blocking practice is a major hassle. This practice of blocking the commercials from the view slows down the rate of return on investment of advertisers. Researchers across the world observed that the major cause of ad blocking is a substantial shrinkage in the user experience. The studies conducted in the direction revealed that privacy concern also led to the ad blocking by online customers. This study covers the major rationales behind the ad blocking practice of the online consumers of Navi Mumbai. In the process, the paper throws enough light on what is considered as absolute wonderful online user experience according to the Navi Mumbai consumers. The study has utilized tools like Crosstab and One-way ANOVA in bringing to light the significant aspects considered by the online consumer of Navi Mumbai in defining what hassle-free user experience and deterrent factors of the same were. The study was conducted between October 2019 and April 2020 through online questionnaires along with interesting telephonic interactions.